Solving Abel's general fuzzy linear integral equations by homotopy analysis method. (2015) - Kumar, Himanshu; Parida, P.K.
The aim of this article is to give a numerical method for solving Abel's general fuzzy linear integral equations with arbitrary kernel. The numerical solution has been obtained by using the method called homotopy analysis method (HAM). The convergence analysis for the proposed method is also given and the applicability of the proposed method is illustrated by solving some numerical examples. The results show the utility and the greater potential of the HAM to solve fuzzy integral equations.